Photocatalytic Activity of LaTi1−xFexO3 Perovskite-Type Oxides Under UV and Visible Light - João Nunes, Maria; Rodrigues, André; Fiadeiro, Paulo; Lopes, Ana; José Pacheco, Maria; Ciríaco, Lurdes (KnE Materials Science, 2022)
LaTi1−xFexO3 (x = 0, 0.2, 0.4, 0.6, 0.8 and 1) perovskite-type oxide samples were synthesized by the solid state reaction method and characterized, and their photocatalytic activity was tested in the degradation of Acid Orange 7 under ultraviolet and visible light. The oxides were successfully synthesized and the XRD results showed a phase change from monoclinic to orthorhombic, with an increase in Fe content (x), with LaTi0.8Fe0.2O3 and LaTi0.6Fe0.4O3 samples presenting both phases. All samples presented low photocatalytic activity under visible light radiation, with a maximum Abs484nm removal of 2.9% for LaFeO3 after one hour. The best results were obtained under ultraviolet radiation, for all samples, with the best photocatalytic activity exhibited by the La2Ti2O7 perovskite, with 44.6% Abs484nm removal after one hour. Keywords: perovskites, LaTi1−xFexO3, photocatalysis, Acid Orange 7